Tinjauan Penjadwalan Proyek Ruas Jalan Nggefak–Oenitas Dengan Metode Lsm (Liniear Scheduling Method) - Lobang, Dorothy Robert; Rizal, Andi Hidayat; Frans, John Hendrik (P3M- Politeknik Negeri Kupang, 2024)
Abstract Project scheduling is a series of activities to determine the stages of work in a project. In the implementation of a project scheduling is a stage that determines the success or failure of a project. Because the project scheduling method is planned so that the implementation of the project runs effectively and efficiently. This study aims to determine the duration of using the NGO method, the duration of the comparison between the NGO method and the duration of the contract of the project and to determine what work can be accelerated due to the use of the NGO method on the Road Improvement Project Nggefak–Oenitas. The NGO method is the appropriate scheduling method if used in repetitive projects, such as in the project to improve the nggefak – Oenitas road section that is repetitive. From the results of the analysis using the NGO method obtained duration to complete the project Nggefak–Oenitas Road Improvement is 138 days, and the comparison of the NGO method and project scheduling is 138 days versus 210 days. And among the work items on the road project there are several jobs that can be accelerated due to the use of NGO methods, among others: preparatory work, ordinary excavation and Stone excavation work, aggregate a foundation layer work, liquid asphalt binder absorption layer work (mechanical), liquid asphalt adhesive layer work/Emulsion, foundation layer Lataston work (HRS–BASE), concrete work F'c 20 Mpa (250) and plain U24 reinforcement steel work. Abstrak Penjadwalan proyek merupakan rangkaian kegiatan untuk menentukan tahapan pekerjaan dalam suatu proyek. Dalam pelaksanaan suatu proyek penjadwalan adalah tahapan yang menentukan berhasil atau tidaknya suatu proyek. Karena metode penjadwalan proyek direncanakan agar pelaksanaan proyek berjalan efektif dan efisien. Penelitian ini bertujuan untuk mengetahui durasi menggunakan metode LSM, durasi perbandingan antara metode LSM dan durasi kontrak dari proyek dan untuk mengetahui pekerjaan apa saja yang dapat dipercepat waktunya akibat penggunaan metode LSM pada Proyek Peningkatan Ruas Jalan Nggefak–Oenitas. Metode LSM adalah metode penjadwalan yang tepat jika digunakan pada proyek yang bersifat berulang, seperti pada proyek Peningkatan Ruas Jalan Nggefak – Oenitas yang bersifat berulang. Dari hasil analisis menggunakan metode LSM diperoleh durasi untuk menyelesaikan proyek Peningkatan Ruas Jalan Nggefak–Oenitas adalah 138 hari, dan perbandingan dari metode LSM dan penjadwalan proyek adalah 138 hari banding 210 hari. Dan diantara item-item pekerjaan pada proyek jalan ada beberapa pekerjaan yang dapat dipercepat waktunya akibat penggunaan metode LSM, antara lain: Pekerjaan Persiapan, Pekerjaan Galian Biasa dan Galian Batu, Pekerjaan Lapis Pondasi Agregat A, Pekerjaan Lapis Resap Pengikat Aspal Cair (Mekanis), Pekerjaan Lapis Perekat Aspal Cair/Emulsi, Pekerjaan Lataston Lapis Pondasi (HRS–BASE), Pekerjaan Beton f'c 20 Mpa (250) dan Pekerjaan Baja Tulangan U24 Polos.